(untitled) (Current Horticulture, 2024)
The study attempts to investigate the presence of structural change in growth of area, production and productivity of selected horticultural crops in India from 1997-98 to 2018-19. The CGR and structural break analysis were employed to examine the growth rates and multiple break periods respectively. The CGR results show that area and production of selected horticultural crops in India grew more during post NHM period than pre NHM period, but there is not a significant growth in productivity of major crops. The structural break analysis shows that shift in growth has been reported after 2005 in selected crops implied that significant growth trend has been observed after NHM implementation. The overall performance in area, production and productivity is quite satisfactory during post-NHM period in major crops except in pepper and tapioca.